Analysis of vocational interests and student’s perception of work-based on society 5.0 towards learning outcomes - Muhammad Anwar (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
The challenge of education in Indonesia with the entry of the era of society 5.0 requires efforts to improve student learning outcomes, especially engineering education students. This paper focuses on looking at the influence of vocational interest on learning outcomes, perceptions of the world of work based on society 5.0 on learning outcomes, and vocational interests and perceptions of the world of work together on learning outcomes. The results of the study found that (1) there was a significant influence between vocational interest on student learning outcomes by 10.3%, (2) there was a significant influence between perceptions of the world of work based on society 5.0 on student learning outcomes by 11.3% and (3) there is a joint influence of vocational interest and perceptions of the world of work based on society 5.0 on student learning outcomes by 16%. Thus, it can be concluded that vocational interest and perceptions about the world of work based on society 5.0 are two factors that contribute to student learning outcomes. This means that the higher the vocational interest and perception of the world of work based on society 5.0, the student learning outcomes will tend to be higher.